Hubungan antara Aktivitas Fisik Kebiasaan Merokok dengan Tingkat Hipertensi pada Lansia - Lapodi, Abd Rijali; Sillehu, Sahrir; Sinay, Herlien; Majida, Narwan (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2024)
AbstractHypertension is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg on two measurements with an interval of five minutes in a state of sufficient rest/quiet. Elderly is part of the final stage of development in the human life cycle. The purpose of this study was to determine the relationship between physical activity and smoking habits with the incidence of hypertension in the elderly in the elderly posyandu, Batu Merah village, the work area of the Air Besar Health Center, Ambon City. The type of research used is quantitative with a descriptive analytical research design with a cross-sectional study method, the sampling technique was carried out using a purposive sampling technique whit predetermined criteria. The total population in this study were all elderly people in the elderly posyandu in Batu Merah village, the working area of the Air Besar Public Health Center and a sample of 102 respondent. Data analysis using Spearman Rho test. Based on the results of the study, physical activity was obtained with p value = 0.000 < 0.05, and smoking habits with p value = 0.000 < 0.05. The conclusion of this study shows that there is a relationship between physical activity and the incidence of hypertension in the elderly at the village health post in Batu Merah, the work area of the Air Besar Public Health Center and there is a relationship between smoking habits and the incidence of hypertension in the elderly at the Posyandu for the elderly in Batu Merah Village, the working area of the Air Besar Public Health Center City Ambon.Keywords: Hypertension, Physical Activity, Smoking Habit, Elderly